2020
DOI: 10.1097/mao.0000000000002431
|View full text |Cite
|
Sign up to set email alerts
|

NF2-Related Intravestibular Schwannomas: Long-Term Outcomes of Cochlear Implantation

Abstract: Objective: Intravestibular schwannomas (IVSs) are uncommon tumors in Neurofibromatosis type 2 (NF2) and are mainly associated with multiple internal auditory meatus (IAM) and cerebellopontine angle (CPA) tumors. They usually induce profound hearing loss which can be rehabilitated by cochlear implantation (CI). The aim of this study was to analyze the longterm outcomes of CI during the unpredictable evolution of NF2 disease. Study Design: Retrospective case review. Setting: Tertiary referral center. Patients: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…Intralabyrinthine schwannomas are tumors of the lateral skull base that can occur spontaneously or as part of an NFII ( 1 ). With the increasing number of patients with unilateral deafness implanted with a cochlear implant and thereforea mandatory MRI in most countries, the occurrence of ILS has received much attention since more cases are found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intralabyrinthine schwannomas are tumors of the lateral skull base that can occur spontaneously or as part of an NFII ( 1 ). With the increasing number of patients with unilateral deafness implanted with a cochlear implant and thereforea mandatory MRI in most countries, the occurrence of ILS has received much attention since more cases are found.…”
Section: Discussionmentioning
confidence: 99%
“…Intra-labyrinthine schwannomas (ILSs) are rare tumors of the lateral skull base and can cause unilateral deafness and can occur in neurofibromatosis type II (NFII) ( 1 , 2 ). These tumors have been classified by Kennedy et al ( 3 ) according to their location.…”
Section: Introductionmentioning
confidence: 99%
“…Intracochlear schwannomas are the most frequent subtype making up for 50 % of all ILS. Bilateral tumors have been described in patients with neurofibromatosis type II [258] and sporadically [259].…”
Section: Epidemiology and Classificationmentioning
confidence: 99%
“…50% die häufigste Gruppe der intralabyrinthären Schwannome dar. Bilaterale ILS wurden sowohl bei Patienten mit Neurofibromatose Typ II 258 als auch sporadisch beschrieben 259 .…”
Section: 411 Epidemiologie Und Klassifikationunclassified
“…Several studies have shown success with cochlear implantation in this population, generally with improved outcomes compared with auditory brainstem implantation (2–6). Although studies are limited, some have also stratified CI outcomes according to treatment modality to inform treatment algorithms for VS with long-term hearing in mind (2–6).…”
Section: Introductionmentioning
confidence: 99%